The Impact of Antibiotics on Latency When Given at the Time of Membrane Rupture before Viability - Lambert, Katherine A.; Cate, Jennifer; Honart, Anne West; Grace, Matthew R.; Dotters-Katz, Sarah K. (American Journal of Perinatology, 2025)
It is well established that antibiotics administered in preterm prelabor rupture of membranes increase latency to delivery. While data are limited for membrane rupture prior to viability, antibiotics may also increase latency in this population. This study aimed to assess the effect of prophylactic antibiotics on the duration of latency in individuals with previable prelabor rupture of membranes.Retrospective cohort of pregnancies with previable prelabor rupture of membranes prior to 230/7 weeks in a single health system (2013–2022). Patients opting for termination or with a contraindication to expectant management were excluded. The primary outcome was latency from previable prelabor rupture of membranes diagnosis to delivery. Secondary outcomes included subanalysis by gestational age as well as maternal and neonatal morbidity and mortality. Bivariate statistics compared patients who did and did not receive antibiotics (ampicillin, gentamicin). Kaplan-Meier/Cox proportional hazards ratios using significant covariates (p < 0.1) in bivariate analysis models examined antibiotic impact on latency.Of 115 patients, 46 (40%) met inclusion criteria, of whom 34 (74%) received latency antibiotics. Median latency did not differ with antibiotic receipt (1 [0.4, 2.6] vs. 0.6 weeks [0.3, 0.9], p = 0.27). When adjusted for gestational age at rupture of membranes, antibiotics were not associated with longer latency (hazard ratio = 1.33 [0.91, 1.93]). Antibiotic receipt was associated with lower rates of previable delivery (23.0, [22.7, 24.0] vs. 21.3 weeks [20.5, 23.1], p = 0.006). Adjusted odds of previable delivery remained lower with receipt of antibiotics (adjusted odds ratio = 0.20, [0.04, 0.90]). Antibiotics were associated with longer latency in patients with rupture of membranes at less than 22 weeks gestation (2.4 [1.3,4.4] vs. 0.6 weeks [0.1,0.9], p = 0.02).Antibiotic administration at the time of previable prelabor rupture of membranes was associated with longer latency prior to 22 weeks gestation. Antibiotic administration increased the odds of delivering after viability. Further study should address optimal antibiotic strategies for this unique population.
Keywords: previable prelabor rupture of membranes; rupture of membranes; latency antibiotics; antibiotic prophylaxis; gestational latency; gestational viability; previable delivery